Cash and crises: No surprises by the virus - Gerhard Rösl; Franz Seitz (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2021)
Despite the increasing use of cashless payment instruments, the notion that cash loses importance over time can be unambiguously refuted. In contrast, the authors show that cash demand increased steeply over the past 30 years. This is not only true on a global scale, but also for the most important currencies in advanced countries (USD, EUR, CHF, GBP and JPY). In this paper, they focus especially on the role of different crises (technological crises, financial market crises, natural disasters) and analyse the demand for small and large banknote denominations since the 1990s in an international perspective. It is evident that cash demand always increases in times of crises, independent of the nature of the crisis itself. However, largely unaffected from crises we observe a trend increase in global cash aligned with a shift from transaction balances towards more hoarding, especially in the form of large denomination banknotes.
urn:nbn:de:hebis:30:3-564471
Keywords: E41; E51; E58; 330; Cash; banknotes; crises; Corona